Love and objectivity in virtue ethics : Aristotle, Lonergan, and Nussbaum on emotions and moral insight - Fitterer, Robert J. (Robert John), 1959- (Lonergan studies., 2008)
Since the Enlightenment, a great deal of ethical philosophy has presumed that rational human beings must set aside their emotions when seeking to make objective and sound moral decisions. Love and Objectivity in Virtue Ethics challenges this presumption, arguing that emotions such as compassion and love are powerful aids in the complex process of attaining objective moral truths in decisions and actions. Drawing on Aristotle's Nicomachean Ethics and the work of Bernard Lonergan and Martha Nussbaum, Robert J. Fitterer tests the assumption that the inclusion of the emotions leads to bias in objective judgments or when determining moral truths. Fitterer first demonstrates how certain cognitive operations set out in Aristotelian virtue ethics can indeed arrive at objective moral truth precisely through the contribution emotions make in moral discernment. Then, drawing on Lonergan's notion of inductive insight, he argues that objectivity is the result of the properly functioning subjectivity of a moral agent. Finally, building on his study of Nussbaum's ethical writings, Fitterer concludes that compassionate love is an attitude that actually fosters the likelihood of discerning and choosing the genuine good, and encourages objectivity in moral decision-making. Richly detailed and argued, Love and Objectivity in Virtue Ethics is a convincing study that involves the works of three of the most important writers on ethics and a passionate appeal to re-examine the process through which humans genuinely make vitally important decisions.